Case Report: Four Cases of Cortical/Brainstem Encephalitis Positive for Myelin Oligodendrocyte Glycoprotein Immunoglobulin G - Wang, Wan; Yin, Juntao; Fan, Zhiliang; Kang, Juxian; Wei, Jia; Yin, Xiaoqian; Yin, Shaohua (Frontiers in Neurology, 2022)
Aim Despite a significant improvement in the number of studies on myelin oligodendrocyte glycoprotein (MOG)-immunoglobulin G (IgG)-associated disorder (MOGAD) over the past few years, MOG-IgG-associated cortical/brainstem encephalitis remains a relatively uncommon and less-reported presentation among the MOGAD spectrum. This study aimed to report the clinical course, imaging features, and therapeutic response of MOG-IgG-associated cortical/brainstem encephalitis. Methods Data of four patients who suffered from cortical encephalitis with epileptic seizures and/or brainstem encephalitis during the course of the disease were retrospectively collected and analyzed. Results In this study, three male patients and one female patient, with a median age of onset of 21 years (ranging 20–51 years) were enrolled. An epileptic seizure was the main symptom of cortical encephalitis in these patients, while the manifestations of brainstem encephalitis were diverse. Cranial MRI demonstrated abnormal signals in unilateral or bilateral cortical or brainstem. Cerebrospinal fluid studies showed normal or mildly elevated leukocyte counts and protein levels, and a cell-based assay detected positive MOG-IgG in the serum of all patients. Two patients were misdiagnosed at the first attack, and both experienced a relapse. All of them accepted the first-line immunotherapy after a confirmed diagnosis and had a good outcome. Conclusion Early suspicion of MOG-IgG-associated encephalitis is necessary for any patient with sudden onset of seizures or symptoms of brainstem damage, especially with lesions on unilateral/bilateral cortical or brainstem on brain MRI.